Dampak penerbitan sukuk dan obligasi konvensional terhadap return saham perusahaan di Indonesia - Nur Indah Hardianti; Agus Widarjono (Jurnal Ekonomi & Keuangan Islam, 2017)
Capital markets are an integral part of economic activity in many countries. One type of capital market is bonds. In Indonesia has developed two types of bonds are syariah-based bonds called sukuk and bonds are not based on sharia. The purpose of this study is to analyze the impact of issuance of sukuk and conventional bonds on stock returns. The company under study is a company that issues both sukuk and syariah bonds. This study uses event study to see the reaction of capital market to the event of issuance of sukuk and conventional bonds. The results showed that the abnormal return of stock is only influenced by variable of maturity value of sukuk and conventional bond. Thus, the stock market is not very responsive to the issuance of sukuk or conventional bonds.